Rotorcraft safety: A simulator-based training perspective - Scaramuzzino, P.F.; Pavel, M.D.; Pool, M.D.; Stroosma, O.; Quaranta, G. (My University, 2021)
Training has the potential to inject a “safety vaccination” into the rotorcraft community by reducing the number of accidents. The term training should not be intended only in a strict sense, i.e., as pilot technical skills training, but more broadly as risk avoidance and safety culture training. As in the case of vaccination, where immunity is created only when applied on a large scale, helicopter accidents will not be eradicated until every player in the rotorcraft community is involved in the safety enhancement process. In particular, as outlined by accident and safety reports, a reduction in the helicopter accident rate cannot be accomplished disregarding pilots’ training and the contribution that flight simulators can provide to both training and certification. This paper provides an overview of the research into simulator training for helicopter pilots conducted as part of the European Joint Doctorate NITROS (Network for Innovative Training on Rotorcraft Safety). An approach that requires an in-depth analysis of the actual training task is adopted for two different maneuvers, namely hover and autorotation. This approach enables the training developer to understand what are the aspects of the actual training situation that should be reproduced in the simulated training situation to avoid ineffective training and negative transfer of skills. Moreover, such an approach allows to identify differences in terms of requirements between the training of basic and advanced maneuvers and between initial and recurrent training. The results of three different pilot-in-the-loop experiments, performed to explicitly confirm the effectiveness of developed training programs and to understand whether certain elements of the simulation can foster the development of superior flying skills, are summarized in this paper.